2021
DOI: 10.1186/s13578-020-00523-y
|View full text |Cite
|
Sign up to set email alerts
|

The crosstalk of HDAC3, microRNA-18a and ADRB3 in the progression of heart failure

Abstract: Background Heart failure (HF) is a clinical syndrome characterized by left ventricular dysfunction or elevated intracardiac pressures. Research supports that microRNAs (miRs) participate in HF by regulating  targeted genes. Hence, the current study set out to study the role of HDAC3-medaited miR-18a in HF by targeting ADRB3. Methods Firstly, HF mouse models were established by ligation of the left coronary artery at the lower edge of the left atria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…HDAC can remove acetyl groups from the amino terminus of lysine residues on histones, while histone acetyltransferases (HATS) promote the addition of lysine residues, leading to structural changes in local chromatin [8,[39][40][41], which is an important step in regulating protein entry into DNA [7]. Studies have shown that HDAC and HATS enzymes are involved in the regulation of transcription Computational and Mathematical in Medicine factors, transcription modulators, and DNA repair proteins [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HDAC can remove acetyl groups from the amino terminus of lysine residues on histones, while histone acetyltransferases (HATS) promote the addition of lysine residues, leading to structural changes in local chromatin [8,[39][40][41], which is an important step in regulating protein entry into DNA [7]. Studies have shown that HDAC and HATS enzymes are involved in the regulation of transcription Computational and Mathematical in Medicine factors, transcription modulators, and DNA repair proteins [42].…”
Section: Discussionmentioning
confidence: 99%
“…Histone deacetylase (HDAC) is a kind of regulation of histone acetylation by protease, the enzyme can be removed from lysine acetyl, and most of the work, by protein complexes formed, is the modification of the chromosome structure and gene expression regulation and control important regulatory factors [ 7 , 8 ]. Conversely, deacetylation can also lead to transcriptional inhibition and impaired hematopoietic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Within this cluster, miR-18a was reported to regulate the expression of several extracellular matrix proteins ( 22 ) and its decreased expression in heart failure in the aged individuals was linked to aging-induced heart remodeling. Corroborating to this, downregulation of miR-18a was associated with increased fibrosis and a decline in heart function ( 23 ), while over-expression of miR-18a reduced fibrosis, hypertrophy, and the apoptosis of cardiomyocytes in heart failure ( 24 ).…”
Section: Introductionmentioning
confidence: 86%
“…In addition, HDAC3 has been shown to promote heart failure and dietary death by exacerbating metabolic disturbances in mitochondria in the cardiomyocytes of mice fed with a high-fat diet [ 78 ]. Mechanically, HDAC3 inhibition prevented heart failure by inhibiting miR-18a-targeted adrenergic-receptor β3 [ 79 ]. HDAC3 expression and activation in cardiomyocytes were also regulated by Ca 2+ /calmodulin-dependent kinase II (CaMKII).…”
Section: The Emerging Roles Of Hdac3 In Solid Organ Injurymentioning
confidence: 99%